"Malignant" Left Ventricular Hypertrophy Identifies Subjects at High Risk for Progression to Asymptomatic Left Ventricular Dysfunction, Heart Failure, and Death: MESA (Multi‐Ethnic Study of Atherosclerosis). Issue 4 (8th February 2018) - Peters, Matthew N.; Seliger, Stephen L.; Christenson, Robert H.; Hong‐Zohlman, Susie N.; Daniels, Lori B.; Lima, Joao A.C.; de Lemos, James A.; Neeland, Ian J.; deFilippi, Christopher R.
Abstract : Background: As heart failure (HF)‐associated morbidity and mortality continue to escalate, enhanced focus on prevention is increasingly important. "Malignant" left ventricular (LV) hypertrophy (LVH): LVH combined with an elevated cardiac biomarker reflecting either injury (high‐sensitivity cardiac troponin T), or strain (amino‐terminal pro‐B‐type natriuretic peptide) has predicted accelerated progression to HF. We sought to determine whether malignant LVH identified community‐dwelling adults initially free of cardiovascular disease at high risk of asymptomatic decline in LV ejection fraction or a clinical cardiovascular event. Methods and Results: A total of 4985 of 6814 individuals without prevalent cardiovascular disease underwent baseline cardiac magnetic resonance for LVH in combination with measurement of plasma high‐sensitivity cardiac troponin T and amino‐terminal pro‐B‐type natriuretic peptide as part of MESA (Multi‐Ethnic Study of Atherosclerosis) and were subsequently divided into 4 groups: (1) No LVH, no elevated biomarkers (n=2206; 44.3%); (2) No LVH, ≥1 elevated biomarkers (n=2275; 45.7%); (3) LVH, no elevated biomarkers (n=153; 3.0%); and (4) LVH, ≥1 elevated biomarkers (malignant LVH; n=351; 7.0%). Cardiac magnetic resonance was repeated 10 years later (n=2831) for assessment of LV ejection fraction <50%. Median follow‐up was 12.2 years. Malignant LVH was associated with 7.0‐, 3.5‐, and 2.6‐fold adjusted increases in incidence of HF, cardiovascular death, and asymptomatic LV dysfunction, respectively, versus group 1. New‐onset HF was predominately HF with reduced ejection fraction (9.5‐fold increase). Conclusions: Malignant LVH is predictive of progression to asymptomatic LV dysfunction, HF (particularly HF with reduced ejection fraction), and cardiovascular death. Consequently, malignant LVH represents a high‐risk phenotype among individuals without known cardiovascular disease, which should be targeted for increased surveillance and more‐aggressive therapies.